PATHS TAKEN FOR MATHEMATICAL ARGUMENTATION IN THE CONSTRUCTION AND USE OF MATHEMATICAL POEMS - Luis Santos, André; José Wharta, Edson (Journal of Interdisciplinary Debates, 2023)
Literary writing is the democratic form of inclusion and development of student aptitude, in which everyone can participate, it is a challenging and stimulating pedagogical activity, in addition to enhancing the development of skills and competencies for meaningful and reflective learning with Mathematics . The school is a space for this “habit-forming force, as it provides those who are directly or indirectly subjected to its influence, not so much particular and particularized thought schemes, but a general disposition that generates particular schemes capable of being applied in different contexts”. different fields of thought and action which can be called cultivated habutus”. (Bourdieu, 2005, p.211). The objective of the article is to present reports of experience of encouraging literary writing with Mathematics with students of the 9th year of Elementary School, stimulating in them the taste for reading and writing with the culture of reading more and writing better, turning to the Mathematics area. The present research also reflects on the importance of the creative didactic transposition of Mathematics contents in the school environment and emphasizes the need for teachers to be equipped to build this knowledge in an innovative and integrated way to the students’ daily lives. in a private teaching unit in Nossa Senhora da Glória, Sergipe, specifically with 9th grade students. The applied methodology is Brainstorming. This technique consists of showing that the student can create a list of ideas on a topic, pointing out everything they can think of on a given topic or subject, transporting it to the types of literary genres: poetry, short stories, chronicles, associating these categories for the universe of Mathematics such as: numbers, geometry, magnitudes and measurements, algebra and statistics. Using mathematical concepts and language for the formulation and writing of texts. Thus contributing for the student to think, do differently, lead to the fantastic world of mathematical knowledge.